Carbon cycling in rice field ecosystems in the context of input, decomposition and translocation of organic materials and the fates of their end products (CO2 and CH4) - Kimura, M.; Murase, J.; Lu, Y.
Rice fields are intensively managed, unique agroecosystems, where soil flooding is general performance for rice cultivation. Flooding the field results in reductive soil conditions, under which decomposition of organic materials proceeds during the period of rice cultivation. A large variety of organic materials are incorporated into rice soils according to field management. In this review, the kind and abundance of organic materials entering carbon cycling in the rice field ecosystem are evaluated first. Then, decomposition of plant residues and soil organic matter in rice fields is reviewed quantitatively. Decomposition of plant residues is shown to be the active process in carbon cycling in rice fields. Rice releases photosynthates into the rhizosphere (rhizodeposition), and they follow a different avenue of decomposition in soil from that of plant residues. Incorporation of rhizodeposition into microbial biomass and soil organic matter during the period of rice cultivation, and their fates after harvesting are evaluated quantitatively from 13C pulse labeled experiments. Percolating water transports inorganic and organic carbon from the plow layer to the subsoil layer. The amounts of their transport and accumulation in the subsoil layer are evaluated in relation to the amounts of soil organic C in the plow layer. Not only CO2 but also CH4 are produced in the decomposition process of organic materials in flooded rice fields. CH4 evolution from rice fields is of global concern from the viewpoint of global warming. Origins of CH4 evolved from rice fields are estimated first, followed by the fates of CH4 in rice field ecosystems. Rhizodeposition is shown to be the main origin of CH4 evolved from rice fields. Evolution to the atmosphere is not the sole pathway of CH4 produced in rice fields. The amounts of CH4 retained in soil, percolated to the subsoil layer and decomposed in soil are evaluated in the context of the amounts of CH4 efflux. Thus, this review focuses on carbon cycling in the rice field ecosystem from the viewpoints of input, decomposition, and translocation of organic materials and the fates of their end products (CO2 and CH4).
Keywords: CARBON CYCLING; CH4; RICE FIELD ECOSYSTEM; RHIZODEPOSITION; STRAW DECOMPOSITION